2012
DOI: 10.1523/jneurosci.0016-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

MEC-17 Deficiency Leads to Reduced α-Tubulin Acetylation and Impaired Migration of Cortical Neurons

Abstract: Neuronal migration is a fundamental process during the development of the cerebral cortex and is regulated by cytoskeletal components. Microtubule dynamics can be modulated by posttranslational modifications to tubulin subunits. Acetylation of ␣-tubulin at lysine 40 is important in regulating microtubule properties, and this process is controlled by acetyltransferase and deacetylase. MEC-17 is a newly discovered ␣-tubulin acetyltransferase that has been found to play a major role in the acetylation of ␣-tubuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 41 publications
4
71
0
Order By: Relevance
“…Four days later, the positions of cells in the cortical wall of the developing somatosensory cortex were examined. Consistent with our previous report [1], at postnatal day 0 (P0), 47% of the neurons expressing the control shRNA (Ctrl shRNA) migrated to the cortical plate (CP) and only 53% remained in the intermediate zone (IZ) and ventricular/subventricular zones (VZ/SVZ) ( Figure 1F). In contrast, 97% of the MEC-17-deficient neurons remained in IZ and VZ/SVZ ( Figure 1F).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Four days later, the positions of cells in the cortical wall of the developing somatosensory cortex were examined. Consistent with our previous report [1], at postnatal day 0 (P0), 47% of the neurons expressing the control shRNA (Ctrl shRNA) migrated to the cortical plate (CP) and only 53% remained in the intermediate zone (IZ) and ventricular/subventricular zones (VZ/SVZ) ( Figure 1F). In contrast, 97% of the MEC-17-deficient neurons remained in IZ and VZ/SVZ ( Figure 1F).…”
supporting
confidence: 91%
“…In particular, acetylation of α-tubulin affects the cell motility and plays an important role in neuronal migration and differentiation [1]. Specifically, acetylation of Lys40 of α-tubulin has prominent impacts on polarized protein trafficking and hence protein transport by promoting the binding of dynein/dynactin and kinesin-1 motor complexes [2,3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this study also revealed that the loss of MEC‐17 (αTAT1) expression leads to microtubule instability, axonal degeneration, and disrupted axonal transport in Caenorhabditis elegans 37. In addition, MEC‐17 (αTAT1) deficiency leads to reduced α‐tubulin acetylation and impaired migration of cortical neurons in mice 38. We found that αTAT1 knockdown by shRNA decreased the expression of acetylated α‐tubulin in vivo and in vitro, which is consistent with the findings observed in C. elegans 37.…”
Section: Discussionmentioning
confidence: 65%
“…During brain development, cortical neurons migrate from the site of their last mitotic division towards their final destination and generate the proper neural circuits [46][47][48]. Proper regulation of microtubule dynamics during axon/leading process formation is crucial for the transition of neurons from the multipolar stage to a bipolar morphology, and is a prerequisite for initiating radial migration [49][50][51]. Tubulins, a number of microtubule-regulating proteins that promote microtubule assembly and proteins that protect microtubules from depolymerization (such as microtubulestabilizing proteins), are all involved in this regulatory process [52].…”
Section: Fgf1functions In Neural Developmentmentioning
confidence: 99%